Hybridized Symbiotic Organism Search Algorithm for the Optimal Operation of Directional Overcurrent Relays. (23rd January 2018) - Sulaiman, Muhammad; Ahmad, Ashfaq; Khan, Asfandyar; Muhammad, Shakoor
Abstract : This paper presents the solution of directional overcurrent relay (DOCR) problems using Simulated Annealing based Symbiotic Organism Search (SASOS). The objective function of the problem is to minimize the sum of the operating times of all primary relays. The DOCR problem is nonlinear and highly constrained with two types of decision variables, namely, the time dial settings (TDS) and plug setting (PS). In this paper, three models of the problem are considered, the IEEE 3-bus, 4-bus, and 6-bus, respectively. We have applied SASOS to solve the problem and the obtained results are compared with other algorithms available in the literature.